TCF7 enhances pulmonary hypertension by boosting stressed natural killer cells and their interaction with pulmonary arterial smooth muscle cells - Li-Wei Wu; Min Chen; Dai-Ji Jiang; Chen-Yu Jiang; Yi-Wei Liu; Bei Feng; Chen-Fei Shi; Xu Huang; Xu Zhang; Xiao-He Xu; Xing-Liang Zhou; Yi Shen; et al. (Respiratory Research)
Abstract Background Pulmonary hypertension (PH) is a life-threatening cardio-pulmonary disorder. Whether natural killer (NK) cells could act as participants in PH and the mechanism by which NK cells moderate pulmonary vascular remodeling has not been fully elucidated. Methods Single-cell RNA sequencing data from lungs of human pulmonary arterial hypertension (PAH) patients and monocrotaline (MCT)-induced PH rat model were retrieved from GEO database or UCSC Cell Browser. Tcf7 conditional knockout mice and TCF7 overexpression following adeno-associated virus 6 (AAV6) intratracheal delivery in rats were generated. The NK92 cell line and primary human pulmonary artery smooth muscle cells (hPASMCs) were used for in vitro experiments. Results Stressed NK cells were much higher in lungs from human PAH and MCT-induced PH compared to corresponding controls. Of note, TCF7 topped the list differentiating high-stressed from low-stressed human NK cells. TCF7-expressing NK cells displayed higher stress profile than TCF7-deficient cells. Tcf7-deficient NK cells exhibited lower Hsp90aa1 and Hsp90ab1 at transcriptional level and Hsp90 at protein level than Tcf7-expressing cells 24 h post-hypoxia. Mechanistically, TCF7-overexpressing NK cells secrete more SPP1 compared to control NK cells, thus promoting the proliferation and migration of hPASMCs 48 h post-hypoxia. TCF7 overexpression in rats aggravated PH features, while Tcf7 deficiency in mice alleviated pulmonary remodeling possibly due to the manipulation of HSP90 level in NK cells and SPP1 in the microenvironment. Conclusions TCF7 contributes to the immunopathology of PH possibly through upregulation of stressed NK cells. Under stress conditions, NK cells promote the proliferation and migration of hPASMC through paracrine effects, thereby further promoting vascular remodeling.